A change management roadmap for wasta‐free managerial practices in Arab organizations. (5th July 2022) - Alsarhan, Fadi
Abstract: Wasta, which is the typical informal network style pervasive in the Arab world, has long been believed to constitute an intrinsic feature of managerial activities and practices in Arab organizations. With a long and intertwined history on one side, and a large widespread on the other, this practice seems near impossible to dissociate from the social and professional landscape of this part of the world. While more and more studies are emerging in order to understand the mechanisms of this practice, the conditions of its emergences, the factors which stand behind its widespread, and the consequences it brings forth, less attention has been directed towards proposing a solution for this problem. Some scholars have nonetheless attempted to offer practical indications on dealing with wasta in order to limit its spread and disintegrate its operational systems. This paper, which falls in line with these works, proposes a roadmap towards a wasta ‐free management system in Arab organizations. Through formulating holistic and comprehensive measures in different levels and areas, this study hopes to contribute a clear roadmap, ready for use by global business leaders, managers, HR practitioners, and government executives alike.